2015
DOI: 10.1101/lm.036590.114
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sleep deprivation and aging on long-term and remote memory in mice

Abstract: Sleep deprivation (SD) following hippocampus-dependent learning in young mice impairs memory when tested the following day. Here, we examined the effects of SD on remote memory in both young and aged mice. In young mice, we found that memory is still impaired 1 mo after training. SD also impaired memory in aged mice 1 d after training, but, by a month after training, sleep-deprived and control aged animals performed similarly, primarily due to remote memory decay in the control aged animals. Gene expression an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 72 publications
(73 reference statements)
1
15
0
Order By: Relevance
“…Acute sleep deprivation and chronic sleep restriction cause significant decrements in short-term and long-term memories in humans and in animal models. [3][4][5][6][7][8][9] In mammals, the consolidation of hippocampal dependent spatial memory is particularly susceptible to the effects of sleep deprivation. [10][11][12] In Drosophila and mouse models, genetic mutants exhibiting reduced sleep also show impairments in memory.…”
Section: Introductionmentioning
confidence: 99%
“…Acute sleep deprivation and chronic sleep restriction cause significant decrements in short-term and long-term memories in humans and in animal models. [3][4][5][6][7][8][9] In mammals, the consolidation of hippocampal dependent spatial memory is particularly susceptible to the effects of sleep deprivation. [10][11][12] In Drosophila and mouse models, genetic mutants exhibiting reduced sleep also show impairments in memory.…”
Section: Introductionmentioning
confidence: 99%
“…A group of young women (20-30 years) were shown to be more vulnerable to 4 hours of sleep loss for 3 nights compared to older women (55-65 years) when tested by psychomotor vigilance test [72]. In a remarkable parallel, rodent studies have shown that sleep deprivation induced memory loss affects young animals more than the older animals [28]. Greater susceptibility of younger individuals that reflect in worsened neurobehavioral parameters post sleep loss might stem from the fact that young age group needs more sleep compared to older individuals.…”
Section: Metabolomics Studies Of Experimental Sleep Deprivationmentioning
confidence: 99%
“…Other molecular processes related to biological aging such as DNA damage response and cellular senescence was also associated to partial sleep deprivation in humans [27]. On the other hand, neurobehavioral studies on younger and older populations have convincingly shown that young individuals are more affected by loss of sleep from perspectives of attention, cognition and learning and memory [28]. Such observation suggests that older individuals are more resistant to effects of sleep loss while younger ones are vulnerable, even demonstrating signatures of "aging-like" characteristics post sleep loss.…”
Section: Introductionmentioning
confidence: 98%
“…The elderly are less tolerant to SD. It has been shown that SD impairs remote memory in aged mice, with changes in gene expression in the hippocampus [9,10]. SD also has detrimental effects on glucose metabolism outside of the brain in peripheral organs.…”
Section: Sleep Deprivationmentioning
confidence: 99%